Bilateral Maxillary Sinus Hypoplasia. (8th December 2014) - Khanduri, Sachin; Agrawal, Sumit; Chhabra, Saakshi; Goyal, Swati
Abstract : Maxillary sinus hypoplasia (MSH) is an uncommon abnormality of paranasal sinuses noted in clinical practice. Computed tomography (CT) scan helps in diagnosing the anomaly along with any anatomical variation that may be associated with it. MSH is usually associated with other anomalies like uncinate process hypoplasia. Three types of MSH have been described. Type 1 MSH shows mild maxillary sinus hypoplasia, type 2 shows significant sinus hypoplasia with narrowed infundibular passage and hypoplastic or absent uncinate process, and type 3 is cleft like maxillary sinus hypoplasia with absent uncinate process. CT and endoscopic examination usually complement each other in diagnosing MSH.